(untitled) (Journal of Hama University, 2019)
disinfection hatching eggs is a basic process and the most widespread method in field is fumigation with formaldehyde which is classified by the World Health Organization as a toxic substance that causes many health problems. As a means of finding a healthy alternative, 400 eggs were collected from breeder’s hatching eggs then divided into four groups The first group consisted of 150 eggs divided into three groups (A1, B1 and C1) with 50 eggs in each group and disinfection with the alcohol propolis extract of the concentrations (5%, 10% and 15%) ,respectively. The second group consisted of 150 eggs divided into three groups (A2, B2, and C2) with 50 eggs in each group and disinfection with the aqueous propolis extract of the concentrations (5%, 10%; 15%), respectively, and the third group is made up of 50 egg disinfected by fumigation with formaldehyde and the fourth group is made up of 50 egg left without disinfection as a witness. The results showed significant differences between treatments at 5% significance among the various disinfectant groups. The efficacy of the alcohol extract, especially at the concentration of 15%, was superior to the effectiveness of formaldehyde as a disinfectant. The water extract did not compete with formaldehyde, But approached its effectiveness at 15% concentration.